Support for e-cigarette regulations among Australian young adults - Michelle I. Jongenelis; Caitlin Kameron; Daniel Rudaizky; Simone Pettigrew (BMC, 2019)
Abstract Background Surveying support for various regulatory options relating to e-cigarettes can assist policymakers to identify those that have broad support and are therefore likely to be easier to implement. However, data on support for potential e-cigarette regulations in Australia are limited. To inform regulatory efforts, the present study assessed attitudes to the regulation of e-cigarettes among Australian young adults, the most prevalent users of e-cigarettes and therefore the most likely population segment to be affected by e-cigarette regulations. Methods A total of 1116 Australians aged 18 to 25 years (59% female) completed an online survey where they were presented with various statements relating to the regulation of e-cigarettes and asked to report on the extent to which they agreed or disagreed with each. Statements presented either a restrictive or non-restrictive approach to e-cigarette regulation. Results Across all statements, 10-22% of respondents responded "don't know" while 23-35% neither agreed nor disagreed, indicating general ambivalence. There was a moderate level of support (33-37%) for regulating e-cigarette sales/use and treating e-cigarettes like tobacco products. Only 20% of respondents were in favour of allowing the use of e-cigarettes in smoke-free areas. Smokers, e-cigarette users, and those who did not believe in the harms associated with e-cigarettes were typically less likely than other respondents to support restrictive approaches. Conclusions The young Australian adults surveyed were somewhat supportive of restrictions around the sale and use of e-cigarettes, but generally opposed outright bans and any need for a prescription from a medical practitioner. Increasing awareness of the harms associated with the use of e-cigarettes represents a potential strategy to gaining regulatory support.